Barriers and Facilitators in Preparation and Consumption of African Indigenous Vegetables: A Qualitative Exploration From Kenya - Merchant, Emily V.; Odendo, Martins; Ndinya, Christine; Nyabinda, Naman; Maiyo, Norah; Downs, Shauna; Hoffman, Daniel J.; Simon, James E. (Frontiers in Sustainable Food Systems, 2022)
Malnutrition and food security continue to be major concerns in sub-Saharan Africa (SSA). It is, for instance, estimated that in Western Kenya, the double burden of malnutrition impacts 19% of adults and 13-17% of households. One potential solution to help address the concern is increased consumption of nutrient-dense African Indigenous Vegetables (AIVs). The objectives of this study were to: (i) document current methods used for preparation and consumption of AIVs; (ii) identify barriers and facilitators of AIVs consumption and preparation; and (iii) identify a package of interventions to increase the consumption of AIVs to promote healthy diets. This study used qualitative data collected from 145 farmers (78 female and 67 male) in 14 focus group discussions (FGDs) using a semi-structured survey instrument. Most farmers reported that they prepared AIVs using the traditional method of boiling and/or pan-cooking with oil, tomato, and onion. However, there were large discrepancies between reported cooking times, with some as little as one to five minutes and others as long as two hours. This is of importance as longer cooking times may decrease the overall nutritional quality of the final dish. In addition, the barriers, and facilitators relative to the food choices of AIVs were contradictory to one another implying that the barriers to preparation and consumption of AIVs are situational and could be modified through context-specific interventions. Key barriers were unavailability and low affordability of AIVs during the dry season, poor taste and monotonous diets, and perceived negative health outcomes (e.g., ulcers, skin rushes). Key facilitators included availability and affordability particularly when self-produced, ease of preparation, and beneficial health attributes (e.g., build blood, contains vitamins and minerals). From these findings, to promote healthy diets within at risk-populations in Western Kenya, interventions to promote the preparation and consumption of AIVs should include improved household production to subsequently improve affordability and availability of AIVs, improved cooking methods and recipes, and the promotion of the beneficial heath attributes of AIVs while actively dispelling the perceived negative health consequences of their consumption.